2022
DOI: 10.1093/jacamr/dlad015
|View full text |Cite
|
Sign up to set email alerts
|

Low self-reported penicillin allergy in South Africa—implications for global public health response

Abstract: Objectives In high-income countries, up to 25% of inpatients have a self-reported penicillin allergy (PA). After testing, 95% of these self-reported PAs are incorrect. These incorrectly labelled PAs increase the use of broad-spectrum antibiotics, and drive bacterial resistance. The epidemiology of PA in low- and middle-income countries is unknown. We aimed to describe the epidemiology and delabelling outcomes of self-reported PA in South African (SA) inpatients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The performance of this study in a high-income setting with relatively low rates of multi-resistant bacterial infections may limit the generalisability of these findings. Furthermore, whilst the prevalence of penicillin allergy labels may be lower in some low/middle-income settings, point-of-care delabelling could still play an important role in settings with limited ambulatory allergy clinic access [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The performance of this study in a high-income setting with relatively low rates of multi-resistant bacterial infections may limit the generalisability of these findings. Furthermore, whilst the prevalence of penicillin allergy labels may be lower in some low/middle-income settings, point-of-care delabelling could still play an important role in settings with limited ambulatory allergy clinic access [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…PEN-FAST is a tool to facilitate the identification of low-risk patients labeled as penicillin allergic. A recent survey from South African hospitals demonstrated that PEN-FAST could also be deployed in a low- and middle-income setting; 65% of hospital-admitted patients presented with a low-risk allergy, making them eligible for a direct penicillin oral challenge . The PALACE trial is an important strategy to improve global access to care and allow safe, fast, and cheap penicillin delabeling strategies to address this important public health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Specialized allergy skin testing is a labor-intensive, expensive, and resource-rich intervention not currently available to large populations of high-income and low-and middleincome countries. 20,21 Furthermore, a penicillin allergy label cannot be removed based on skin testing alone, and the oral challenge remains the gold standard. PEN-FAST is a tool to facilitate the identification of low-risk patients labeled as penicillin allergic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, true penicillin allergy is uncommon in our region, therefore the majority of patients who report having a penicillin allergy are actually not at high risk of a severe allergic reaction. 66 Importantly, alternative therapeutic options are available in most cases. It is therefore important to take a good history and work-up of anyone reporting penicillin allergy; penicillin desensitisation before syphilis treatment can be attempted in those with a confirmed severe allergy, although this is generally only necessary for cases of neurosyphilis and syphilis in pregnancy, where the efficacy of non-beta-lactam drug options is not well-established.…”
Section: Therapeutic Principlesmentioning
confidence: 99%